Preventive Role of Thymoquinone against Certain Chronic Health Issues: A Review - Palwasha Khalil; Sara Masood; Attiq Rehman; Faiza Khalil; Javeria Nawaf (International Journal of Nutrition Sciences, 2020)
The seed of Nigella sativa commonly called ‘black seed’ has been used in different civilizations for centuries to treat various animal and human diseases. Thymoquinone is chemically 2-methyl-5-isopropyl-1, 4-benzoquinone monoterpene molecule and it is the main constituent in black seeds responsible for most of the pharmacological characteristics. The current review aims to discuss the effect of thymoquinone based on experimental evidence in reducing the risk of certain chronic issues such as cancer, diabetes, cardiovascular diseases, nephropathy, retinopathy, neuropathy, hepatopathy, hypertension, and obesity in the shadow of available literature. However, clinical trials are recommended to prove the studied effects of thymoquinone in humans.